Rechargeable Micro‐Batteries for Wearable and Implantable Applications. Issue 9 (15th June 2022) - Li, Pengzhou; Liao, Meng; Li, Jiaxin; Ye, Lei; Cheng, Xiangran; Wang, Bingjie; Peng, Huisheng
Abstract : The rise of wearable and implantable microelectronics calls for the corresponding high‐performance micropower sources. Rechargeable micro‐batteries (MBs) are considered the most promising candidate due to their high energy density and stable voltage output. To date, various MBs with different configurations have been designed to meet the ever‐growing high energy consumption requirements of microelectronic devices. Therefore, it is very urgent to summarize the current challenges of MBs and discuss solutions for future research. In this perspective, a comprehensive overview and insights on rechargeable MBs are carefully presented with an emphasis on the design of various configurations. The representative preparation methods and application scenarios of various MBs have been summarized. The challenges and future perspectives are also discussed to provide insights into the forward‐looking research and potential directions of this promising field. Abstract : The recent advance in rechargeable micro‐batteries (MBs) for wearable and implantable applications has been carefully presented with an emphasis on the design of various configurations.